Evaluasi Keberhasilan SIPINTER sebagai Sistem Layanan Informasi di Perpustakaan DPR RI menggunakan Model Delone dan McLean - Rizal, Khairul; Wicaksono, Hendra; Wardiyono, Wardiyono; Wati, Mustika (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2025)
The Integrated Current Information Package System Sistem Paket Informasi Terkini (SIPINTER) is an integrated information service at the Library of the House of Representatives of the Republic of Indonesia (DPR RI), providing various information resources related to the duties and functions of the DPR RI. The system has been operating since 2020 to support literacy and research needs within the DPR RI. However, to date, no feedback has been provided by users who have accessed SIPINTER, either through a dedicated survey or through the website’s own survey feature, making it difficult to assess the system’s utilization and optimization. This study was conducted to evaluate the extent to which SIPINTER has been successful for users of the DPR RI Library by applying the DeLone and McLean model. A quantitative method with a correlational approach was employed to measure the influence among variables and to test the hypotheses. The findings indicate that three out of the seven proposed hypotheses were accepted, as the relationships showed path coefficient values below 0.05 and t-test values above 1.96. These accepted relationships include: system quality on system use, information quality on user satisfaction, and system use on user satisfaction. This study concludes that the success of SIPINTER is primarily determined by the quality of the system and the quality of the information provided, while the service quality aspect has not shown a significant influence. These findings indicate that improving service quality is an essential factor in optimizing the utilization of SIPINTER and offer new insights into the application of the DeLone and McLean model within the context of a legislative library.